Two-Color Green Fluorescent Protein Time-Lapse Imaging. (November 1998) - Ellenberg, Jan; Lippincott-Schwartz, Jennifer; Presley, John F.
The Aequorea victoria green fluorescent protein (GFP) is widely recognized as a powerful tool in cell biology, serving as a vital reporter for monitoring localization and dynamics of intracellular proteins and organelles over time. GFP variants with shifted spectral characteristics have been described and offer enormous potential for double-labeling experiments and protein-protein interaction studies. However, most GFP variant combinations are not suitable for double-label, time-lapse imaging experiments because of either extremely rapid photobleaching of blue-shifted GFP variants or crossover of their excitation and emission spectra, which must then be computer corrected. Here, we describe the successful use of two photostable spectral GFP variants, W7 and 10C, in dual-color, timelapse imaging of fusion proteins in living cells using either wide-field or confocal microscopy. W7 and 10C were highly photostable during repetitive long-term imaging and were cleanly separated by their different excitation spectra alone with negligible crossover of fluorescence. We present time-lapse image sequences of COS-7 cells co-expressing both a marker of the Golgi complex (galactosyl transferase) fused to W7 and a marker of the nuclear envelope (lamin-B receptor) fused to 10C. To our knowledge, these image sequences provide the first simultaneous visualization of Golgi and nuclear envelope membranes in living cells.